Impact of SMART Pass filter in patients with ajmaline-induced Brugada syndrome and subcutaneous implantable cardioverter-defibrillator eligibility failure: results from a prospective multicentre study. Issue 5 (9th September 2021) - Conte, Giulio; Cattaneo, Fabio; de Asmundis, Carlo; Berne, Paola; Vicentini, Alessandro; Namdar, Mehdi; Scalone, Antonio; Klersy, Catherine; Caputo, Maria Luce; Demarchi, Andrea; Özkartal, Tardu; Salghetti, Francesca; et al.
Abstract: Aims: Ajmaline challenge can unmask subcutaneous implantable cardioverter-defibrillator (S-ICD) screening failure in patients with Brugada syndrome (BrS) and non-diagnostic baseline electrocardiogram (ECG). The efficacy of the SMART Pass (SP) filter, a high-pass filter designed to reduce cardiac oversensing (while maintaining an appropriate sensing margin), has not yet been assessed in patients with BrS. The aim of this prospective multicentre study was to investigate the effect of the SP filter on dynamic Brugada ECG changes evoked by ajmaline and to assess its value in reducing S-ICD screening failure in patients with drug-induced Brugada ECGs. Methods and results: The S-ICD screening with conventional automated screening tool (AST) was performed during ajmaline challenge in subjects with suspected BrS. The S-ICD recordings were obtained before, during and after ajmaline administration and evaluated by the means of a simulation model that emulates the AST behaviour with and without SP filter. A patient was considered suitable for S-ICD if at least one sensing vector was acceptable in all tested postures. A sensing vector was considered acceptable in the presence of QRS amplitude >0.5 mV, QRS/T-wave ratio >3.5, and sense vector score >100. Of the 126 subjects (mean age: 42 ± 14 years, males: 61%, sensing vectors: 6786), 46 (36%) presented with an ajmaline-induced Brugada type 1 ECG. Up to 30% of subjects and 40% of vectors failed the screening during the appearance of Brugada type 1 ECG evoked by ajmaline. The S-ICD screening failure rate was not significantly reduced in patients with Brugada ECGs when SP filter was enabled (30% vs. 24%). Similarly, there was only a trend in reduction of vector-failure rate attributable to the SP filter (from 40% to 36%). The most frequent reason for screening failure was low QRS amplitude or low QRS/T-wave ratio. None of these patients was implanted with an S-ICD. Conclusion: Patients who pass the sensing screening during ajmaline can be considered good candidates for S-ICD implantation, while those who fail might be susceptible to sensing issues. Although there was a trend towards reduction of vector sensing failure rate when SP filter was enabled, the reduction in S-ICD screening failure in patients with Brugada ECGs did not reach statistical significance. Clinical trial registration: https://clinicaltrials.gov Unique Identifier NCT04504591.